Risk factors influencing fall risk in geriatric patients with type 2 diabetes: a comprehensive analysis - Muharrem Bayrak; Kamber Kaşali; Merve Güner; Kenan Cadirci; Adil Furkan Kılıç; Dogan Nasır Binici (The Aging Male)
Background and objectives Type 2 diabetes mellitus (T2DM) is a common chronic disease in the elderly. Comorbidities, especially neuropathy and retinopathy, significantly increase fall risk in this group. This study aimed to identify fall risk factors in older adults with T2DM.Materials and methods From January to June 2024, 242 T2DM patients aged 65 and older were followed at the internal medicine outpatient clinic. Fall risk was assessed using the Performance Oriented Mobility Assessment (POMA), Hendrich II Fall Risk Model (HIIFRM), Barthel Activities of Daily Living Index, and Clinical Frailty Scale (CFS).Results Among the patients (median age = 70 years), 41.3% had experienced at least one fall in the previous year. Factors, such as age and diabetes duration were associated with falls. Notably, hypoglycemia (aPR: 1.90, p = 0.017), polypharmacy (aPR: 2.39, p = 0.004), osteoarthritis (aPR: 2.48, p = 0.017), (aPR: 1.70, p = 0.025), and malnutrition (aPR: 1.90, p = 0.007) were independently associated with fall risk.Conclusions Fall risk in elderly outpatients with T2DM was linked to various factors, including hospitalization, malnutrition, osteoarthritis, polypharmacy, neuropathy, and hypoglycemia. To mitigate this risk, patient-specific care plans are recommended.